It's the tone, stupid! Soft information in credit rating reports and financial markets. (2nd July 2021) - Kiesel, Florian
Abstract: Using a unique, comprehensive data set of 6110 Moody's rating reports from 2004 to 2019, I find that the textual tone of credit rating reports has a significant effect on the credit default swap (CDS) and stock markets. This effect is driven by negative watchlist reports. The results show that the negative tone of these watchlist reports, in particular, leads to a widening in CDS spreads and lower abnormal stock returns. It also indicates that the rating is likely to be downgraded. These findings show the importance of credit rating agencies as information sources for financial markets.